Accessory Hepatic Veins and Their Surgical Implication - Lucas A. S. Pires; Carlos A. A. Chagas; Leite; Marcio A. Babinski (Academia Anatomica International, 2017)
Vascular variations regarding the hepatic veins are well explored in the literature. Many of these variations possess clinical and surgical relevance due to the fact that liver transplants, hepatectomies, and tumors resection of the liver are still a challenge to medical professionals. Furthermore, a great number of diseases affect the vascular dynamic of such organ. During regular dissection of a male cadaver fixed with a 10% formalin solution, we found a rareanatomical variation wherethree veins emerged from the parenchyma of the visceral side of the fifth portal hepatic lobe and drained into the inferior vena cava above the renal vein confluence. We report this rare vascular anomaly and assess its clinical and surgical significance